PROSPECTS OF CONVERGENCE OF SCIENCES FOR SOLVING THE PROBLEMS OF CRITICAL AREAS OF THE BIOSPHERE - Alexander A. Chibilev; Sergey V. Levykin; Boris I. Kochurov; Grigoriy V. Kazachkov (Юг России: экология, развитие, 2019)
Aim. The aim is to show the relevance of the convergence of basic science in order to solve global environmental problems. Discussion. Solving the problems of critical areas of the biosphere which requires the combined efforts of various sciences and fields of knowledge is considered as an objective prerequisite for convergence. This article was written on the basis of the findings of our own long-term studies of the steppes of Northern Eurasia and central Arctic landscapes on relic loess-ice lithogenic basis, compared with historical and literary data. From the standpoint of steppe studies, two critical areas of the biosphere are distinguished: steppe zone of Eurasia and tundra of the Arctic which are justified as axes of convergence. The steppe studies are considered as a center of convergence around these axes with the possible formation of a new superdisciplinary field of knowledge and practice, steppenomy, in perspective. Nature-like technologies based on the principle of the co-creation of man and nature, aimed at overcoming the crisis phenomena in ecosystems and attaining high stability and productivity, are considered as an innovation product of the steppenomy. Conclusion. The spread and development of pasture ecosystems in various climatic zones is one of the priorities of constructive co-creation of man and the biosphere. An increase in tundra productivity and creation of “beef belts” in the steppes of Eurasia are regarded as a constructive analogue of Tselina, recreating grass ecosystems as a neo-hyperzonal phenomenon on tens of millions of hectares. In addition to contributing to the solution of the food problem, the pasture arrangement of the last territorial reserve under convergent scientific support will contribute to the global ecological restoration of the Earth’s unique ecosystems.